Clarifying essential terminology in entrustment. (3rd July 2021) - Schumacher, Daniel J.; Cate, Olle ten; Damodaran, Arvin; Richardson, Denyse; Hamstra, Stanley J.; Ross, Shelley; Hodgson, Jennie; Touchie, Claire; Molgaard, Laura; Gofton, Wade; Carraccio, Carol; ,
Abstract: With the rapid uptake of entrustable professional activties and entrustment decision-making as an approach in undergraduate and graduate education in medicine and other health professions, there is a risk of confusion in the use of new terminologies. The authors seek to clarify the use of many words related to the concept of entrustment, based on existing literature, with the aim to establish logical consistency in their use. The list of proposed definitions includes independence, autonomy, supervision, unsupervised practice, oversight, general and task-specific trustworthiness, trust, entrust(ment), entrustable professional activity, entrustment decision, entrustability, entrustment-supervision scale, retrospective and prospective entrustment-supervision scales, and entrustment-based discussion. The authors conclude that a shared understanding of the language around entrustment is critical to strengthen bridges among stages of training and practice, such as undergraduate medical education, graduate medical education, and continuing professional development. Shared language and understanding provide the foundation for consistency in interpretation and implementation across the educational continuum.